Case 3437: Vipera latastei Boscá, 1878 (Reptilia, Serpentes): proposed conservation of the spelling of the specific name over Vipera latasti Boscá, 1878. - Santos, X; Brito, J C; Alonso-Zarazaga, M A (Bulletin of Zoological Nomenclature)
The Case was withdrawn by the authors. A subsequent application to conserve the spelling of the specific name latastei Boscá, 1878 as published in the binomen Vipera latastei was submitted as Case 3629 (acknowledgement of receipt published in BZN 70 (2): 70; published in BZN 71 (1): 22–25), for which Opinion 2381 has been issued (see BZN 73 (2–4): 145–147). The Case is now closed.